Repeated propofol exposure-induced neuronal damage and cognitive impairment in aged rats by activation of NF-κB pathway and NLRP3 inflammasome - Liu, Peng-fei; Gao, Teng; Li, Tian-zuo; Yang, Yi-tian; Xu, Yong-xing; Xu, Zhi-peng; Mi, Wei-dong (Neuroscience letters, 2021)
•200 mg/kg propofol treatment (intraperitoneal injection, i.p.) every 9 days, with a total of 6 times did not affect the cognition of the aged rats.•200 mg/kg propofol treatment i.p.) every day, with a total of 6 times impaired the cognition of the aged rats.•Propofol induced cognitive dysfunction partly through the activation of NF-κB pathway and NLRP3 inflammasome.•Bay 11-7082, an inhibitor of NF-κB, could attenuate the neuroinflammation and cognition injury caused by daily propofol treatment. Elderly patients receive propofol at regular intervals for sedation during gastrointestinal endoscopy. However, the link between cognition and intermittent propofol exposure remains unclear. Thus, we used aged rats to investigate the effect of propofol on cognition. The study included two parts. In the first part, aged (18–20 months old) male Sprague-Dawley rats underwent intermittent intraperitoneal injection of propofol (200 mg/kg) or intralipid, every 9 days or once a day. In the second part, some aged rats received intraperitoneal injection of Bay 11-7082 (1 mg/kg), a specific inhibitor of NF-κB, 30 min before propofol injection. Memory tests were performed to evaluate cognition 24 h after the entire treatment. The hippocampal neuronal damage was assessed by TUNEL staining. The hippocampal levels of p-NF-κB p65, NLRP3, caspase-1 p20, and cleaved caspase-3 were detected by western blotting. The hippocampal and serum levels of IL-1β, IL-6, and TNF-α were evaluated using ELISA. There were no differences in the behavioral tests, hippocampal neuronal damage, and neuroinflammation between groups given intralipid and propofol treatment every 9 days. However, repeated propofol treatment once a day promoted activation of NF-κB and the NLRP3 inflammasome, inducing cognitive impairment and neuroinflammation. Interestingly, pretreatment with Bay-11-7082 not only inhibited NF-κB/NLRP3 inflammasome activation, but also attenuated neuronal damage and cognitive dysfunction in aged rats exposed to daily propofol treatment. Intermittent propofol treatment every 9 days may be safe for aged rats. However, propofol treatment once a day could impair the cognition of aged rats, partly through the activation of the NF-κB pathway and NLRP3 inflammasome, which may be a potential targets for the treatment of cognitive impairment in elderly patients.